Costs and benefits of renewables portfolio standards in the United States. (December 2015) - Barbose, Galen; Bird, Lori; Heeter, Jenny; Flores-Espino, Francisco; Wiser, Ryan
Abstract: Most state renewables portfolio standard (RPS) policies in the United States have five or more years of implementation experience. Understanding the costs and benefits of these policies is essential for RPS administrators tasked with implementation and for policymakers evaluating changes to existing or development of new RPS policies. This study estimates and summarizes historical RPS costs and benefits, and provides a critical examination of cost and benefit estimation methods used by utilities and regulators. We find that RPS compliance costs constituted less than 2% of average retail rates in most U.S. states over the 2010–2013 period, although substantial variation exists, both from year-to-year and across states. Compared to RPS costs, relatively few states have undertaken detailed estimates of broader societal benefits of RPS programs, and then only for a subset of potential impacts, typically some combination of avoided emissions and human health benefits, economic development impacts, and wholesale electricity market price reductions. Although direct comparison to RPS cost estimates is not possible, the available studies of broader RPS benefits suggest that in many cases these impacts may at least be of the same order of magnitude as costs, highlighting a need for more refined analysis.